If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+7+(9/(2x-1))=0
Domain of the equation: (2x-1))!=0We multiply all the terms by the denominator
x∈R
2x*(2x-1))+(9+7*(2x-1))=0
We multiply parentheses
2x*(2x-1))+(9+14x+=0
We add all the numbers together, and all the variables
14x+2x*(2x-1))+(9=0
| 6+c/2=4 | | 5n+n=6n | | 7x+4=5x=20 | | -6(x-6)+10x=30 | | X+14+x-17+6x-5=180 | | B÷2+5=2b | | 1/3j+9=0 | | X+14+x-17=6x-5 | | 6x-5+x+14+x-17=180 | | 6x-5+x+14=x-17 | | 180=2x+5x+3x+50 | | x=2x+5x+3x+50 | | 7x-10+2x+5+2x+9=180 | | 55x-25=10x+20 | | -2=9x+12 | | 3x-5x+88x=4x+18 | | 14x-10x=3x | | -6x-2=3x+12 | | 4x-(75-x)=125 | | 4^x-8=1/1024 | | r=7/6r | | 3x+2x=7x-x | | 40+5x+x=180 | | 6a-3/2=9/2 | | 4/7x+2=22 | | 10x+80=160 | | 3(n+2)=8 | | 4+5b-2b^2=5 | | 0=3x-20- | | 1/3(x-9)=1 | | (3x+2)=82 | | 0=3x-20 |